Decoding the impact of gut microbiota on heart failure - Shuhong Zhao; Lingxuan Dan; Rong Huang; Zhuoyu Shen; Dan Huang; Pan Wu; Zhenguo Ma (Genes and Diseases)
Decreased cardiac output in heart failure leads to intestinal ischemia and increased permeability. Substantial changes occur in the gut microbiota, characterized by a decline in beneficial bacteria and an overgrowth of potentially harmful bacteria. The gut microbiota is intricately linked to prevalent risk factors for heart failure, including hypertension, diabetes, obesity, and renal insufficiency. Furthermore, imbalanced microbiota-derived metabolites enter the bloodstream and may contribute to the progression of heart failure. Ongoing research explores gut microbiota manipulation to alleviate heart failure with probiotics, targeted antibiotics, fecal microbiota transplantation, and dietary adjustments. This review summarizes how gut microbiota participates in heart failure and highlights the emerging promise of modulating gut dysbiosis as a therapeutic approach for managing heart failure.